KCl‐induced high temperature corrosion of selected commercial alloys: Part I: chromia‐formers. Issue 12 (16th July 2015) - Kiamehr, S.; Dahl, K. V.; Montgomery, M.; Somers, M. A. J.
Abstract : Laboratory testing of selected chromia‐forming alloys was performed to rank the materials and gain further knowledge on the mechanism of KCl‐induced high temperature corrosion. The investigated alloys were stainless steels EN1.4021, EN1.4057, EN1.4521, TP347H (coarse‐grained), TP347HFG (fine‐grained), Sanicro 28 and the nickel‐based alloys 625, 263 and C276. Exposure was performed at 600 °C for 168 h in flowing N2 (g)+5%O2 (g)+15% H2 O(g) (vol.%). Samples were covered with KCl powder prior to exposure. A salt‐free exposure was also performed for comparison. Corrosion morphology and products were studied with scanning electron microscopy (SEM), energy dispersive X‐ray spectroscopy (EDS) and X‐ray diffractometry (XRD). It was observed that in the salt‐free exposure, stainless steels TP347H (coarse‐grained) and EN1.4521 failed to form a thin protective oxide layer compared to the oxide formed on the other alloys. In the presence of solid KCl, all the alloys showed significant corrosion. Measurement of corrosion extent indicated that alloys EN1.4057, Sanicro 28 and 625 show a better performance compared to the industrial state of the art material TP347HFG under laboratory conditions. An additional test was performed with KCl vapor in static air for the same duration and at the same temperature. This was undertaken to investigate the role of the vapor phase and revealed that KCl vapor at 600 °C can initiate attack.